Cyanine‐Like Boronic Acid‐Derived Salicylidenehydrazone Complexes (Cy‐BASHY) for Bioimaging Applications. Issue 62 (1st October 2020) - Santos, Fábio M. F.; Domínguez, Zoe; Fernandes, João P. L.; Parente Carvalho, Cátia; Collado, Daniel; Pérez‐Inestrosa, Ezequiel; Pinto, Maria V.; Fernandes, Adelaide; Arteaga, Jesús F.; Pischel, Uwe; Gois, Pedro M. P.
Abstract: Boronic acid‐derived salicylidenehydrazone complex (BASHY) dyes with a polymethine backbone were designed to yield efficient red‐emitting and two‐photon absorbing fluorophores that can be used as markers for astrocytes. The dyes are chemically stable in aqueous solution and do not undergo photodecomposition. Their photophysical properties can be electronically fine‐tuned and thereby adapted to potentially different imaging situations and requirements. Abstract : The best of both worlds : BASHY (boronic acid‐derived salicylidenehydrazone complexes) dyes were structurally and electronically integrated with a polymethine backbone, yielding novel fluorophores with highly interesting photophysical properties. The dyes show polarity‐sensitive emission in the red spectral range, significant two‐photon absorption, and improved (photo)chemical stability. They can be designed for bioimaging.